PEMANFAATAN MEDIA PEMBELAJARAN DARING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH TSANAWIYAH RAUDHATUL ULUM NGIJO KARANGPLOSO - King Tarqy Al Mahdy; Mohammad Afifulloh; Atika Z. Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This article aims to review the use of social media in learning PAI in MTs Raudhatul Ulum Karangploso. Data from this study was obtained from observations, interviews and documentation. The results of this study show that only certain social media are used in PAI learning. The problem of social media utilization is the unfulfillment of facilities and infrastructure both in schools and in their homes. In addition, not all social media can be utilized by parents and teachers. Only certain social media used in learning is social media that is used daily. This shows that the utilization of social media in PAI learning has not been maximized so that educational institutions are expected to prepare for this pandemic by utilizing social media in learning by paying attention to the level of understanding of its users. Keyword: Benefit, Sosial Media , PAI learning